The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s0102-05362008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade produtiva e econômica do consórcio entre chicória e rúcula em função da época de plantio

Abstract: Segundo Yokota (2002), nas áreas que se concentram próximo aos centros consumidores, sobretudo nos cinturões verdes das grandes cidades, a produção das hortaliças é realizada na modalidade de jardinagem oriental. Este modelo caracteriza-se pelo uso intensivo do solo e da mão-de-obra, e as principais hortaliças cultivadas são o tomate, a cenoura e as folhosas, entre as quais a chicória e a rúcula.Recentemente, pesquisas têm proposto o cultivo consorciado de hortaliças. Neste, além da maior produção de alimentos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Dentre as possibilidades de consórcio entre hortaliças, verificadas em pesquisas, podemos citar alface com rúcula (Costa et al, 2007); chicória com rúcula (Cecílio Filho et al, 2008); cenoura com rúcula (Lima, 2008); pepino com alface (Rezende, 2008); cebola com alface (De Paula et al, 2009) e brócolis com alface (Ohse et al, 2012). Nesses trabalhos, essas espécies apresentaram adequado desempenho agronômico, com produtividade superior a obtida em monocultivo, indicando o sistema consorciado como alternativa viável economicamente, além de melhor uso eficiente da terra.…”
Section: Introductionunclassified
“…Dentre as possibilidades de consórcio entre hortaliças, verificadas em pesquisas, podemos citar alface com rúcula (Costa et al, 2007); chicória com rúcula (Cecílio Filho et al, 2008); cenoura com rúcula (Lima, 2008); pepino com alface (Rezende, 2008); cebola com alface (De Paula et al, 2009) e brócolis com alface (Ohse et al, 2012). Nesses trabalhos, essas espécies apresentaram adequado desempenho agronômico, com produtividade superior a obtida em monocultivo, indicando o sistema consorciado como alternativa viável economicamente, além de melhor uso eficiente da terra.…”
Section: Introductionunclassified
“…When evaluating the cost of production and profitability of lettuce, radish, arugula and cabbage cultivated as a single crop and intercropped with sweet pepper, Rezende et al (2008) observed a greater impact of inputs on TOC when compared to manpower. Although these authors did not evaluate packaging and transportation costs, this behavior differed from that observed in the present study, where the labor force had a higher impact than inputs.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of return (RR) per real (R$) invested was obtained through the relationship between GI and TOC. The profitability index (PI) was obtained from the relationship between NI and GI and expressed as a percentage, according to Cecílio Filho et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Cecílio Filho et al (2008) assessed chicory and rocket intercropping depending on the rocket sowing season in relation to chicory transplant. In the intercropping system, where the species are sown and transplanted on the same day, chicory reached the culture line of the rocket after the 33 rd day, of 40 days of the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Costa (2006) assessed lettuce and rocket intercropping in function of cropping season and the rocket sowing time in relation to the transplant of three lettuce cultivars and observed that the LER of the intercropping systems ranged from 1.08 to 2.02, indicating that there was better use of the environmental resources and/or products, compared to the single cropping. Cecílio Filho et al (2008) assessed the productive and economic viability of chicory and rocket intercropping depending on the season when the intercropping was established and also observed that all the intercropping systems assessed were shown to be viable from the point of view of the LER, ranging from 1.31 to 2.29. Rocket has been used as a secondary crop in vegetable intercropping because it has a short cycle, low/short stand and erect growth.…”
Section: Resultsmentioning
confidence: 99%